Towards Sustainable City: A Covering Model for Recycling Facility Location-allocation in Nilai, Malaysia - Zati Aqmar Zaharudin; Adibah Shuib; Rieske Hadianti; Zahari Md Rodzi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Sustainable waste management is essential for any nation. To limit the amount of waste transported to landfills, it is critical to handle waste properly, notably by segregating recyclables from discarded waste. Waste separation at the source is critical to ensure that generated waste is not completely directed to landfill. The practice of waste separation would initiate the recycling process, which is able to reduce the amount of waste sent to the landfill. Recycling is critical to the achievement of two Sustainable Development Goals (SDGs), 11 and 12, for which Malaysian government has set the goal for recycling rates to reach 40% by 2025 in 2022, the rate has reached 33.17%. In Malaysia, recyclables are either collected on-site or sent to a designated facility. The separation at source activity is essential for developing recycling practices. Despite being the largest waste generator, public engagement, particularly at the household level, has remained low, most likely due to recycling facility availability and accessibility issues. Thus, improving public access to the facility would lead to increased recycling rates. In this study, a mixed integer linear programming model is proposed to locate recycling facilities in optimal locations that cover the most amount of waste generated by households. The capacity level is induced to ensure that the dropped-off recyclables are proportionate at the designated facility locations. Several experiments were conducted for validity purposes, and the proposed model was applied in a Malaysian urban area, namely Nilai. As a result, the proposed model was able to locate the optimal locations with the requisite capacity level while ensuring coverage for most Nilai households.